PERANCANGAN SISTEM INFORMASI PEMASARAN HASIL PERTANIAN (SIRAHAN) DI DINAS PERTANIAN TANAMAN PANGAN DAN HORTIKULTURA PROVINSI KALIMANTAN BARAT - Fauzan Asrin; Maswadi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2022)
The agricultural products of food crops and horticulture in West Kalimantan Province need to be marketed or published to the broader community even though they have great potential. As the era of the industrial revolution 4.0 requires all areas of human life to move from conventional activities to digital activities, a digitalization effort is urgently needed to expand the marketing of agricultural products. The Agricultural Product Marketing Information System (SIRAHAN) of the West Kalimantan Food Crops and Horticulture Service is here to respond to the industrial revolution era 4.0. This system was designed to promote and inform quickly, precisely and accurately existing agricultural products and offer farming convenience in the digital era to create a food-secure society. The research was conducted using a qualitative descriptive approach with literature studies on SIRAHAN. The SIRAHAN design is an information system business process that will provide services in cultivating food crops and horticulture. The system development life cycle waterfall method with unified modelling language (UML) will help see user behaviour in using the information system. SIRAHAN is a marketplace that provides services for all farming business needs. Seeing the potential benefits of SIRAHAN, which are significant to support the expansion of marketing of various agricultural products, the Regional Government, through the Provincial Agent of Food Crops and Horticulture of West Kalimantan, is expected to continue to develop and optimize this information system.